2021
DOI: 10.1021/jacs.1c06403
|View full text |Cite
|
Sign up to set email alerts
|

Design of High-Performance Lead-Free Quaternary Antiperovskites for Photovoltaics via Ion Type Inversion and Anion Ordering

Abstract: The emergence of halide double perovskites significantly increases the compositional space for lead-free and air-stable photovoltaic absorbers compared to halide perovskites. Nevertheless, most halide double perovskites exhibit oversized band gaps (>1.9 eV) or dipole-forbidden optical transition, which are unfavorable for efficient single-junction solar cell applications. The current device performance of halide double perovskite is still inferior to that of lead-based halide perovskites, such as CH3NH3PbI3 (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 88 publications
2
35
0
Order By: Relevance
“…Inorganic antiperovskite nitrides with X 3 AN formula (X is a divalent cation and A is a trivalent anion) are emerging compound semiconductors with a potential application in solar‐energy conversion 24,32,33 . To enable the potential application, an understanding of the fundamental properties relevant for PV applications is important, but it has not been established yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic antiperovskite nitrides with X 3 AN formula (X is a divalent cation and A is a trivalent anion) are emerging compound semiconductors with a potential application in solar‐energy conversion 24,32,33 . To enable the potential application, an understanding of the fundamental properties relevant for PV applications is important, but it has not been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…31 Inorganic antiperovskite nitrides with X 3 AN formula (X is a divalent cation and A is a trivalent anion) are emerging compound semiconductors with a potential application in solar-energy conversion. 24,32,33 To enable the potential application, an understanding of the fundamental properties relevant for PV applications is important, but it has not been established yet. In this study, using density functional theory (DFT) calculations, we scrutinize the crystal structure, electronic band structure, and optical absorption of Sr 3 MN and Ba 3 MN (M = Sb or Bi), potential PV absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are 3, 6, and 3 different configurations for x = 0.25, 0.50, and 0.75 (see Figure a–c), respectively. The total energy difference between different configuration is smaller than 11 meV/atom, suggesting the possibility of forming disordered solid solutions . It is shown that although the band gap differs between different configurations for a certain x , the band gap of Mg 3 NAs 1– x Bi x alloys generally decreases with increasing x , reduced from 2.102 eV in Mg 3 NAs to 0.612 eV in Mg 3 NBi (see Figure d).…”
Section: Results and Discussionmentioning
confidence: 91%
“…The total energy difference between different configuration is smaller than 11 meV/atom, suggesting the possibility of forming disordered solid solutions. 46 It is shown that although the band gap differs between different configurations for a certain x, the band gap of Mg 3 NAs 1−x Bi x alloys generally decreases with increasing x, reduced from 2.102 eV in Mg 3 NAs to 0.612 eV in Mg 3 NBi (see Figure 6d). This decreasing trend is associated with the higher Bi p orbitals than As p orbitals.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…33 In addition, the calculated static dielectric constant and optical absorption coefficient of Cs 4 GeGe 2 Br 12 are close to those typical of double perovskites (e.g., Cs 2 AgBiBr 6 ). 14 We believe that our work expands the family of mixed-valence halide perovskites and provides a new idea for potential optoelectronic semiconductor design.…”
mentioning
confidence: 99%